Credit constraints and structure: a theoretical model of extractivism and slow-growth dynamics - LEOPOLDO GÓMEZ-RAMÍREZ; NESTOR GARZA (Brazilian Journal of Political Economy, 2021)
ABSTRACT We develop a theoretical model that explains the relationship between credit constraints and economic growth in the context of a three-sector economy, including an “extractive” sector. The model belongs in the structuralist tradition and it is inspired by the Colombian economy. In contrast to neoclassic development economics models, we prove that: 1) relaxing the credit crunch would foster formal sector growth but it may nevertheless not imply formal employment growth; and 2) the economy can converge to a pattern where the extractive sector increases while the formal one shrinks.